The influence of vehicle body type in shaping behavioural intention to acquire electric vehicles: A multi-group structural equation approach. (October 2018) - Mohamed, Moataz; Higgins, Christopher D.; Ferguson, Mark; Réquia, Weeberb J.
Highlights: We investigate behavioral factors influencing individual mindset towards EVs. A multi-group structural equation model is carried out for seven vehicle body types. Psychological beliefs are dominant predictors of EV adoption. Potential adopters of EV are not one homogenous group across vehicle body types. Potential Luxury and Pickup EV buyers are the most distinct groups. Abstract: The study presents a multi-group structural equation modelling exercise to identify differences in the mindset of individuals towards electric vehicles (EVs) across seven vehicle body types in Canada. The study utilizes a sample of 15, 392 households and grounds the psychographic orientation of potential EV adopters on an extended version of the Theory of Planned Behaviour. Specifically, the study measures the impact of five latent constructs; environmental concerns, attitude, subjective norm, personal moral norm, and perceived behavioural control on the intention to adopt EVs along with socio-economic-demographic (SED) variables. The results highlight that both attitude and perceived behaviour control are the strongest factors influencing individual intention to adopt EVs. However, the multi-group invariance analysis indicates that the psychographic orientation and the SED traits of potential adopters of different EV body types are significantly different, with particular standouts in the luxury and pickup truck classes. We follow this up with an analysis of mindshare towards EVs over the seven vehicle types. Insights derived from the analysis can help define potential submarkets for EVs and accelerate their adoption.